2018
DOI: 10.1101/265801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Escherichia colican survive stress by noisy growth modulation

Abstract: Gene expression can be noisy 1,2 , as can the growth of single cells 3,4 . Such cell-to-cell variation has 7 been implicated in survival strategies for bacterial populations [5][6][7] .

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
(93 reference statements)
3
15
0
Order By: Relevance
“…Growth rate fluctuations have also been observed in single cells across many bacterial species 2,8,[18][19][20] . They can arise due to temporal variation in the expression of metabolic enzymes 2 , the expression of burdensome proteins 12 , and due to regulatory effects such as feedback involved in cell size control 19 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Growth rate fluctuations have also been observed in single cells across many bacterial species 2,8,[18][19][20] . They can arise due to temporal variation in the expression of metabolic enzymes 2 , the expression of burdensome proteins 12 , and due to regulatory effects such as feedback involved in cell size control 19 .…”
Section: Introductionmentioning
confidence: 97%
“…Genes involved in adaptation to stress are among the noisiest genome-wide 3,5 . Studies on individual pathways have revealed specific examples in which heterogeneous expression of stress response genes can allow subpopulations of cells to survive sudden environmental stress, such as transient exposure to antimicrobial drugs, oxidative stress, and acid stress [6][7][8][9] . Recent studies also indicate that heterogeneity in the expression of genes involved in DNA repair can lead to variability in mutation rates, contributing to microbial evolution [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient stress is a strong trigger of phenotypic diversification that can be eventually used for controlling the degree of diversification of a bacterial population. Previous studies have shown that such phenotypic diversification mechanisms are governed by a complex set of physiological mechanisms involving noise in gene expression, metabolism and growth (Kiviet et al ., ; Kleijn et al ., ; Patange et al ., ), these three mechanisms being highly cross‐correlated and being controlled through mutual feedback loops. Ultimately, the superimposition of these three mechanisms leads to population phenotypic heterogeneity that can in turn confer interesting functionalities to the whole population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Noisy gene expression is known to be beneficial under conditions that are stressful or are prone to change. This lets a cell hedge its bet and adapt to changing scenarios [6][7][8][9][10]. Study of the effects of noise on gene expression can therefore lead to a better understanding of the phenotypic variability in these systems.…”
Section: Introductionmentioning
confidence: 99%